Pengaruh Penggunaan Aplikasi Zoom sebagai Media Komunikasi Belajar Mahasiswa Ilmu Komunikasi Universitas Islam Nusantara Sumatera Utara - Alfian, Alfian; Achiriah, Achiriah; Rasyid, Abdul (Medan Resource Center, 2022)
This study aims to find out how the Effect of Using the Zoom Application as a Communication Media on the Learning Activity Process of Communication Studies Students at UIN North Sumatra. The theory used by the author is the theory of New Media and Uses And Effects. The object of this research is the user of the Zoom application as a communication medium in the online learning process. The method used is a quantitative correlation method with a single table data analysis technique and hypothesis testing. Then the results obtained through Hypothesis Testing that the Effect of Using the Zoom Application as a Communication Media on the Learning Activity Process of Communication Science Students at UIN North Sumatra shows a correlation coefficient (rho) of 0.450 with a significance number of 0.000, which means H0 is rejected if the value is <0.05 and Ha received. With the strength of the influence of variable X on variable Y of 20, %. So there is an influence as a communication medium of 20% between the use of the Zoom application on the learning activities of students in Communication Science at UIN North Sumatra.